Liraglutide 3 mg on weight, body composition, and hormonal and metabolic parameters in women with obesity and polycystic ovary syndrome: a randomized placebo-controlled-phase 3 study - Elkind-Hirsch, Karen E.; Chappell, Neil; Shaler, Donna; Storment, John; Bellanger, Drake (Fertility and sterility, 2022)
To study the efficacy and safety of the GLP-1 analog liraglutide 3 mg (LIRA 3 mg) vs. placebo (PL) for reduction of body weight (BW) and hyperandrogenism in women with obesity and polycystic ovary syndrome (PCOS). Randomized, double-blind, placebo-controlled trial. Hospital-based outpatient endocrine and metabolic center. Women diagnosed with PCOS (NIH criteria) were randomly assigned to LIRA 3 mg (n = 55) or PL (n = 27) once daily for 32 weeks with lifestyle intervention. Study visits at baseline and 32 weeks included BW and body composition by dual-energy x-ray absorptiometry. Oral glucose tolerance tests were done with sex steroids, free androgen index (FAI), and lipids measured in the fasting sample. The primary end points were changes in BW and FAI. Safety was assessed in all patients who received at least one dose of the study drug. Change in BW from baseline to week 32 was −5.7% (±0.75) with LIRA 3 mg vs. -1.4% (±1.09) with PL. At week 32, more participants on LIRA 3 mg than on PL achieved at least 5% weight reductions (25 of 44 vs. 5 of 23). Free androgen index significantly reduced with LIRA 3 mg compared with the PL where the mean FAI slightly increased. Gastrointestinal events, which were mostly mild to moderate, were reported in 58.2% of the LIRA 3 mg-subjects and 18.5% of PL subjects. LIRA 3 mg once daily appears superior to PL in reducing BW and androgenicity and improving cardiometabolic parameters in women with PCOS and obesity. NCT03480022. Liraglutida 3 mg sobre el peso, composición corporal y parámetros hormonales y metabólicos en mujeres obesas con síndrome de ovario poliquístico: estudio de fase 3 aleatorizado controlado con placebo. Estudiar la eficacia y seguridad del análogo GLP-1 Liraglutida 3 mg (Lira 3 mg) vs placebo (PL) para la reducción del peso corporal (BW) y el hiperandrogenismo en mujeres obesas y con síndrome de ovario poliquístico (PCOS). Ensayo aleatorizado, doble ciego, controlado con placebo. Centro endocrino y metabólico hospitalario ambulatorio. Se aleatorizó a las mujeres con diagnóstico de PCOS (criterios NIH) asignándose a LIRA 3 mg (n=55) o PL (n=27) una toma diaria durante 31 semanas además de intervención en el estilo de vida. Las visitas al incluirse en el estudio y a las 31 semanas incluyeron BW y composición corporal medida por absorciometría de Rayos X con energía dual. Se realizaron test en ayunas de tolerancia a la glucosa con esteroides sexuales, índice de andrógenos libre (FAI) y medida de lípidos. El objetivo primario fueron los cambios en el BW y en el FAI. Se evaluó la seguridad en todas las pacientes que recibieron al menos una dosis del fármaco en estudio. El cambio en el BW entre la visita basal y la semana 32 fue de -5.7% (+/-0.75) con LIRA 3 mg vs -1.4% (+/-1.09) con PL. En la semana 32 más pacientes con LIRA 3 mg que con PL consiguieron una reducción del peso de al menos el 5% (25 de 44 vs 5 de 23). El índice libre de andrógenos se redujo de manera significativa con LIRA 3 mg comparado con PL, en cuyas pacientes el FAI medio aumentó ligeramente. Se informó de efectos adversos gastrointestinales, mayoritariamente de ligeros a moderados en el 58.2% de sujetos con LIRA 3mg frente al 18.5% de sujetos con PL. LIRA 3 mg en una única toma diaria parece superior al placebo en la reducción del BW y androgenicidad y en la mejora de los parámetros cardiometabólicos en mujeres con PCOS y obesidad.